2017
DOI: 10.1002/ece3.2775
|View full text |Cite
|
Sign up to set email alerts
|

Flight performance in the altricial zebra finch: Developmental effects and reproductive consequences

Abstract: The environmental conditions animals experience during development can have sustained effects on morphology, physiology, and behavior. Exposure to elevated levels of stress hormones (glucocorticoids, GCs) during development is one such condition that can have long‐term effects on animal phenotype. Many of the phenotypic effects of GC exposure during development (developmental stress) appear negative. However, there is increasing evidence that developmental stress can induce adaptive phenotypic changes. This hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
0
5
1
Order By: Relevance
“…However, although the study was performed during the reproductive period of the species when we would expect a preference for the scent of the best potential partner, our results show that females avoided the scent of males with greater body condition and body size. Our results are difficult to explain in a sexual context because males with better body condition may have a greater reproductive success [51]. Furthermore, previous evidence has found an overall preference of females for males of better body condition and size [52], although other studies have found assortative mating in this species [53,54].…”
Section: Discussioncontrasting
confidence: 57%
“…However, although the study was performed during the reproductive period of the species when we would expect a preference for the scent of the best potential partner, our results show that females avoided the scent of males with greater body condition and body size. Our results are difficult to explain in a sexual context because males with better body condition may have a greater reproductive success [51]. Furthermore, previous evidence has found an overall preference of females for males of better body condition and size [52], although other studies have found assortative mating in this species [53,54].…”
Section: Discussioncontrasting
confidence: 57%
“…Indeed, developmental stress has been shown to have persistent effects on numerous phenotypic traits across many life‐history stages. Some examples of the broad range of phenotypic traits altered by developmental conditions include: animal performance (Chin et al ., ; Crino et al ., ), body size (Pavlovska‐Teglia et al ., ), behaviour (Spencer & Verhulst, ) and cognitive ability (Nowicki, Searcy & Peters, ; Farrell et al ., ). Furthermore, recent meta‐analyses have also shown that specific types of developmental stress (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, although the study was performed during the reproductive period of the species, when we would expect a preference for the scent of the best potential partner, our results showed that females avoided the scent of males with a higher body condition, i.e., greater body mass and body size. Our results are difficult to explain in a sexual context because males with better body condition may have greater reproductive Birds 2024, 5 132 success [53]. Furthermore, previous evidence has found an overall preference of females for males with better body condition and size [54], although other studies have found assortative mating in this species [55,56].…”
Section: Discussionmentioning
confidence: 56%